Security Model for the Internet of Things, Through Blockchain - Díaz Gutiérrez, Yesid; Cueva-Lovelle, Juan Manuel; Candia Herrera, Diana Carolina (UNIR, 2026)
Due to the proliferation of computer crimes related to information vulnerability handled by people and entities and evidenced in attacks of financial, commercial, personal and even family nature; a need has been identified to implement, security strategies and protocols in each and every one of these areas, which make possible the effective protection of the integrity and privacy of data. Regarding this, there are protection schemes such as cryptography and reliable time stamping which undoubtedly have managed to partially solve this problem by attacking structural and crucial points. However, the evolution in the technology field has been currently represented in the fourth industrial revolution and its context towards 4.0 technologies and smart industries; various technologies have been positioned in the emerging and disruptive categories, among which the Internet of Things (IoT) stands out. This technology has become the target of multiple computer attacks, due to the processes of Extraction, Transformation, Loading and Transmission of large volumes of data. Alongside its widespread connection to the Internet, it’s become a strategic target for such attacks. A possible alternative solution to this situation is blockchain, which allows information to be public and stored in different blocks, which makes it easier to guarantee the integrity of information based on the following aspects: • Identification of the attacked and / or compromised information, which can be marked as invalid information. • Public report of the attack. • Information backup in another block to facilitate its recovery. In this regard, it is important to highlight that these functional and technological characteristics offered by the blockchain, facilitate the management of information and its integrity. However, it is necessary and essential to previously guarantee the structure of the information generated; as some processes of Business Intelligence (BI), such as the Extraction, Transformation and Load scheme (ELT), would be of great relevance and support during the development of this procedure.
Keywords: Blockchain; Business Intelligence; Cryptography, Immutability; Internet of things; Referencing; Safety; Smart Industries